A High-Availability Bebras Competition System - Kristan, Nataša; Gostiša, Dean; Fele-Žorž, Gašper; Brodnik, Andrej (Informatics in Schools. Teaching and Learning Perspectives, 2014)
In this paper we present a new system that can be used for the Bebras and related competitions. The system supports both non-interactive tasks consisting of a question and multiple choice answers and standardized interactive tasks. It also contains a highly versatile administration interface permitting individual teachers/mentors to organize their own competitions (class-wide, school-wide, ...) that can be used in teaching of informatics. Furthermore, the system is also highly scalable and can be distributed across multiple servers. We have successfully evaluated the system in multiple competitions, some with over 10,000 students. Because it is designed to support i18n, it was easily localized and used in Slovenia and in Serbia.